2018
DOI: 10.1007/s13593-018-0509-3
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable management of nitrogen nutrition in winter wheat through temporary intercropping with legumes

Abstract: Wheat-legume temporary intercropping with legume devitalization in late winter can increase the N self-sufficiency of cropping systems and improve the N nutrition of wheat as a cash crop. However, this practice has been scarcely investigated. In this study, carried out in a Mediterranean environment with cold winters, we compared 14 treatments over 3 years with different weather patterns: (A) pure stands of common wheat (Triticum aestivum L.) grown at 0, 40, 80, 120, 160 kg N ha −1 ; (B) pure stands of faba be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…An increasing attention is given to intercropping in agroecology to better value resources and to decrease the use of synthetic inputs (i.e., fertilizers, pesticides). In wheat-pea intercropping, reports indicated the promotion of nitrogen nutrition of wheat ( Ghaley et al, 2005 ; Bedoussac and Justes, 2010a ; Guiducci et al, 2018 ) and suggested a promotion of iron nutrition for pea ( Zuo and Zhang, 2009 ), and of phosphorus nutrition for both plant species ( Li et al, 2003 , 2007 ; Hinsinger et al, 2011 ). The possible contribution of rhizosphere microbiota of plants to these beneficial effects mostly remains to be untapped.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing attention is given to intercropping in agroecology to better value resources and to decrease the use of synthetic inputs (i.e., fertilizers, pesticides). In wheat-pea intercropping, reports indicated the promotion of nitrogen nutrition of wheat ( Ghaley et al, 2005 ; Bedoussac and Justes, 2010a ; Guiducci et al, 2018 ) and suggested a promotion of iron nutrition for pea ( Zuo and Zhang, 2009 ), and of phosphorus nutrition for both plant species ( Li et al, 2003 , 2007 ; Hinsinger et al, 2011 ). The possible contribution of rhizosphere microbiota of plants to these beneficial effects mostly remains to be untapped.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the rainfall from November 2014 to January 2015 was higher than from November 2015 to January 2016 (Figs 1 and 2). In 2016, both temperature and precipitation conditions probably led to a higher availability of N in the soil compared to 2015, thus promoting the rapid growth of barley [38, 17]. When the barley gains a competitive advantage in terms of growth during the initial stages of the growth cycle, this advantage remains for the rest of the growth cycle as well [39].…”
Section: Resultsmentioning
confidence: 99%
“…“Arkta”). This mixture was chosen on the basis of previous studies carried out at the University of Perugia, which showed a high ecological complementarity between these two species in terms of both light and N resources, and a consequent high and constant biomass production of the mixture [16, 17]. The cover was sown in the two years on 31 October 2014 and on 26 October 2015, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Wheat production in INT was the most variable across years, and such variability was associated with high N loss from the system when the climatic conditions were favorable to N leaching (high rainfall after side-dress fertilization and/or slow crop growth as recorded in the former two years, Figure 1). TIC was proved to reduce N leaching loss as compared to traditional management in organic wheat production [19,22]. Non-inversion soil management is known for reducing nutrient loss [36], thus its combination with TIC was expected to significantly improve the N retention in ORG+.…”
Section: Discussionmentioning
confidence: 99%
“…Durum wheat was grown as the sole crop in the INT and ORG (single rows 0.15 m apart); in ORG+, durum wheat was temporary intercropped (TIC, Guiducci et al [19]) with faba bean (Vicia faba L. var. minor Beck.…”
Section: Durum Wheatmentioning
confidence: 99%